Measurement of cosmic ray positron and negatron spectra between 50 and 800 MeV - Daugherty, J. K.; Hartman, R. C.; Schmidt, P. J. (1974)
A magnetic spectrometer employing digital-readout spark chambers and a gas Cerenkov threshold counter was used to measure the spectra of cosmic ray negatrons and positrons over the range from 50 to 800 MeV during two balloon flights from Ft. Churchill, Manitoba, in July 1972. A preliminary analysis of data from the first flight suggests that the total electron spectrum in this range has not fully recovered to its condition at solar minimum observed in 1965. The preliminary results also provide upper limits for the positive fraction over the range from 200 to 800 MeV which are consistent with the values found in earlier measurements.